THE EFFECT OF SMARTPHONE BASED EDUCATION MEDIA ON CHILDBIRTH PREPARATION IN THE COVID-19 PANDEMIC PERIOD IN SURABAYA - Mardliyana, Nova Elok; Puspita, Irma Maya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Indonesia is one of the countries affected by the COVID-19 outbreak. This condition has an impact on many sectors, including maternal and neonatal health services, which usually provided by face-to-face, temporarily had to be postponed to prevent the spread of the virus. Providing health services during the COVID-19 pandemic by health workers can take advantage of information and communication technology. On of the education media that can used is by sending video via smartphone, because that is effective and easily media without contact so as to prevent the spread of the COVID-19. This study aims to determine the effect of the educational media provided via smartphones on preparation for childbirth during the COVID-19 pandemic in Surabaya. This study used a quasy experimental design with a pretest-postest. The size of samples were 35 respondents of pregnant women in the 1st, 2nd, and 3rd trimesters who live in Surabaya. The statistical test used Paired Samples T-Test. The results of the analysis of this study indicate that the p value is 0.001